Building Discipline Through Healthy Lifestyle Behaviors: “Shared Lunch Education” for Early Childhood - Hardiningrum, Andini; Rihlah, Jauharotur; Rulyansah, Afib; Firdaus, Firdaus; Aliya, Nur Idhofi (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to analyze the phenomenon of discipline through the habit of healthy living in early childhood by examining the patterns, forms, and indicators that emerge in healthy routines, the impact of healthy living behaviors on children’s independence and sense of responsibility, and parental support. Methodology: This study used a descriptive qualitative approach with observation sheets, interview guidelines, and documentation as instruments. The research subjects were nine children aged 3-4 years. Data were obtained through direct observation, recorded semi-structured interviews, field notes, and photographic documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was strengthened through source and technique triangulation. Main Findings: The results of the study show that discipline and healthy living behaviors are formed through routine habits, teacher role modeling, consistent school culture, and parental support. Children demonstrate disciplined behavior by willingly following rules, eating independently, and taking responsibility for cleaning up their eating utensils. Healthy living behaviors practiced by children include washing their hands with soap, using clean eating utensils, and brushing their teeth after meals. Novelty/Originality of this study: This study offers new insights into the process of internalizing discipline and healthy lifestyle behaviors in early childhood through school routines, teacher consistency, and parental support at home. These findings emphasize the importance of school culture synergy, teacher role modeling, and family support in forming the foundation for sustainable positive behaviors from an early age.